Cost‐consequence analysis of an intervention for the management of neuropsychiatric symptoms in young‐onset dementia: Results from the BEYOND‐II study. (7th November 2019) - van Duinen‐van den IJssel, Jeannette C.L.; Bakker, Christian; Smalbrugge, Martin; Zwijsen, Sandra A.; Adang, Eddy; Appelhof, Britt; Zuidema, Sytse U.; de Vugt, Marjolein E.; Verhey, Frans R.J.; Koopmans, Raymond T.C.M.
Abstract : Objective: To evaluate the cost‐consequences of an intervention for the management of neuropsychiatric symptoms in nursing home residents with young‐onset dementia. Methods: A stepped wedge design was used. The intervention consisted of an educational program and a multidisciplinary care program and was implemented in 13 nursing homes from September 2015 to March 2017. Costs' outcomes included the time investment of the elderly care physician and health care psychologists regarding the management of neuropsychiatric symptoms, residents' psychotropic drug use, nursing staff absenteeism, and costs of the educational program. Composite cost measure contained the sum of costs of staff absenteeism, costs on psychotropic drugs, and costs of the educational program. Costs of time investment were investigated by comparing means. Costs of psychotropic drug use were analyzed with mixed models at resident level and as part of the composite cost measure on unit level. Staff absenteeism was also analyzed at unit level. Results: Compared with care as usual, the mean costs of time invested decreased with €36.79 for the elderly care physician but increased with €46.05 for the health care psychologist in the intervention condition. Mixed model analysis showed no effect of the intervention compared with care as usual on the costs of psychotropic drug use, staff absenteeism, and the composite cost measure. The costs of the educational program were on average €174.13 per resident. Conclusion: The intervention did not result in increased costs compared with care as usual. Other aspects, such as the lack of a structured working method, should be taken into account when considering implementation of the intervention.